Plan de manejo ambiental de residuos líquidos industriales y los riesgos asociados de seguridad y salud en el trabajo por el manejo de los mismos, en La Cía. Hotelera Andes Plaza Bogotá D.C. (2017)
This grade job is focused on the development of managing plan of the dangerous residues that is use as an alternative for the manage of that Andes Plaza hotel´s residues. Everything into environmental frame that generes the less negative impact and preserving the healthy´s employees that are near to this sustances. One of the misionalprocess of the Andes´s hotel is the food and drinking which produces the two types of the residues (vegetal used oil and mud of trap ´s fat) that will be objects of the study of this job. Even with a plan of manage of solid residues that are consolitaded, for the vegetal used oil and mud of trap ´s fat don’t exist a gestion management that garantice a final storage and disposition and according with the rules in force tending to avoid alterations in the healthy space and part´s affectations. For development of this plan we are going to analyse the actual situation that frames the activities of management of that residues, it will be based on a study of impacts, dangers, and risks. This project will be the entrance relation for development of itself, moreover, the verification of the legal requiriments associates for giving suitable fulfillment, in this way can comply with the expectatives of the high management of everything interesting parts.